The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/and.14521
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the therapeutic options for diabetes‐associated male infertility as illustrated in animal experimental models

Abstract: Diabetes is a rising global health concern and an increasingly common cause of male infertility. Although the definitive pathophysiological mechanisms underpinning the association between diabetes and infertility is unclear, there are several animal studies showing diabetes to be a detrimental factor on reproductive health through apoptosis, oxidative stress and impairment of steroidogenesis. Furthermore, as reflected in animal models, antidiabetic strategies and relevant treatments are beneficial in the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Twenty seminiferous tubules from each sample were magnified at 400× to determine the testicular maturity and damage using the Johnsen's tubular biopsy score (JTBS) method [117]. Each seminiferous tubule was given a score between 1 and 10 to indicate its level of germinal epithelial maturity according to the following description: score (1), no cells appear in the tubular section; score (2), no germ cells exist; score (3), just the spermatogonia can be seen; score (4), limited primary spermatocytes; score (5), numerous primary spermatocytes but no spermatozoa or spermatids; score (6), only a few spermatids; score (7), a large number of early spermatids deprived of differentiation; score (8), a few differentiated spermatids; score (9), several differentiated spermatids; and finally, score (10), regular tubules with lots of sperms.…”
Section: Histological Study On the Testesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty seminiferous tubules from each sample were magnified at 400× to determine the testicular maturity and damage using the Johnsen's tubular biopsy score (JTBS) method [117]. Each seminiferous tubule was given a score between 1 and 10 to indicate its level of germinal epithelial maturity according to the following description: score (1), no cells appear in the tubular section; score (2), no germ cells exist; score (3), just the spermatogonia can be seen; score (4), limited primary spermatocytes; score (5), numerous primary spermatocytes but no spermatozoa or spermatids; score (6), only a few spermatids; score (7), a large number of early spermatids deprived of differentiation; score (8), a few differentiated spermatids; score (9), several differentiated spermatids; and finally, score (10), regular tubules with lots of sperms.…”
Section: Histological Study On the Testesmentioning
confidence: 99%
“…Multiple body organs are affected by micro-and/or macrovascular diabetic complications, resulting in their damage, dysfunction, and eventual failure [4,5]. Reproductive dysfunction is one of the adverse effects of diabetes in both humans and animal models [6][7][8][9]. Recently, it was reported that type 1 and type 2 diabetes (T1DM and T2DM, respectively) adversely affected the sperm quality and histopathology of reproductive organs in T1DM and T2DM mice with a great extent of similarity.…”
Section: Introductionmentioning
confidence: 99%